2004
DOI: 10.1373/clinchem.2003.022848
|View full text |Cite
|
Sign up to set email alerts
|

[13C]Nandrolone Excretion in Trained Athletes: Interindividual Variability in Metabolism

Abstract: Background: Nandrolone is one of the most abused anabolic steroids, and its use in doping is increasing, as revealed by numerous positive cases during recent years in various sports. Different authors have reported the possible natural production of nandrolone metabolites in humans, and some of these authors argued that exhaustive exercise could increase nandrolone production in the body or induce dehydration and consequently lead to an increase of nandrolone metabolites in urine. Methods: Volunteers (n ‫؍‬ 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
6
22
0
Order By: Relevance
“…Isotope ratio mass spectrometry and gas chromatography coupled to mass spectrometry were used to detect variations of the testosterone metabolites compounds (Baume et al 2006). Nandrolone metabolites (19-norandrosterone and 19-noretiocholanolone) stemming from the metabolism of 19-norandrostenedione (Bricout and Wright 2004) were also quantiWed in order to support previously published results (Baume et al 2004) on the nandrolone metabolites pharmacokinetics (manuscript in preparation).…”
Section: General Considerationsmentioning
confidence: 91%
“…Isotope ratio mass spectrometry and gas chromatography coupled to mass spectrometry were used to detect variations of the testosterone metabolites compounds (Baume et al 2006). Nandrolone metabolites (19-norandrosterone and 19-noretiocholanolone) stemming from the metabolism of 19-norandrostenedione (Bricout and Wright 2004) were also quantiWed in order to support previously published results (Baume et al 2004) on the nandrolone metabolites pharmacokinetics (manuscript in preparation).…”
Section: General Considerationsmentioning
confidence: 91%
“…These findings confirmed the difference in the kinetics of elimination of the labeled nandrolone already observed elsewhere. 21,23 The P values obtained with the ANOVA test revealed that the 19-NA concentration increased significantly after effort on day 11 for 7 participants (P , 0.05), decreased for 3 participants (P , 0.05), and remained constant for 3 participants (P . 0.05).…”
Section: -Na and 19-ne Concentrations Before And After Physical Effmentioning
confidence: 98%
“…All volunteers (34) provided informed consent for the participation in the study. Other aspects pertaining to the selection of the volunteers were in accordance with Baume et al 21 Two doses of 25 mg 3,4-13 C 2 -nandrolone were orally administered at a 24-hour interval to 22 of the selected healthy male volunteers, and the remaining 12 participants were administered placebo. Volunteers were randomly selected to receive labeled nandrolone or placebo.…”
Section: Study Protocolmentioning
confidence: 99%
“…19 nortestosterone and its metabolites in meat also produce some other important adverse effects, such as cardiomyopathy, coronary artery disease, peliosis hepatitis, hepatic carcinogenicity, cholestasis, hypoproteinemia, adrenal atrophy, cerebral dysfunction, and emotional instability (mood swings, aggressiveness depression, psychosis addiction etc. ), testicular shrinkage, sperm count and sperm motility, alterations in sperm morphology, decreased semen production, infertility, prostatic hypertrophy, prostatic carcinoma, gynecomastia, menstrual cycle disorders, masculinization, deepening of the voice, shrinkage of the breasts, male-pattern baldness and an increase in sex drive, acne, body hair and clitoris size, uterine atrophy, breast atrophy [5][6][7][8] . As their possible harmful effects result from the intake of hormone residues and their metabolites, usage of growth-promoting drugs for fattening livestock have been banned in many countries.…”
mentioning
confidence: 99%